2021
DOI: 10.3390/nu13124488
|View full text |Cite
|
Sign up to set email alerts
|

The Vitamin D Decrease in Children with Obesity Is Associated with the Development of Insulin Resistance during Puberty: The PUBMEP Study

Abstract: Obesity and cardiometabolic risk have been associated with vitamin D levels even in children. The objective of the present study was to evaluate the association between insulin resistance (IR), cardiometabolic risk factors, and vitamin D in children from prepubertal to pubertal stages. A total of 76 children from the PUBMEP study, aged 4–12 years at baseline, were included. Children were evaluated in prepubertal and pubertal stages. Anthropometric measurements and selected cardiometabolic risk biomarkers, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…This study was conducted within the context of the multicenter PUBMEP study in Spain “Puberty and metabolic risk in children with obesity”, previously published [9, 10]. Here, a sub-population of 119 pubertal children (54 boys and 65 girls) from the whole PUBMEP cohort was selected for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted within the context of the multicenter PUBMEP study in Spain “Puberty and metabolic risk in children with obesity”, previously published [9, 10]. Here, a sub-population of 119 pubertal children (54 boys and 65 girls) from the whole PUBMEP cohort was selected for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Obesity-related insulin resistance and low-grade chronic inflammation seem to be the most important predictive factors for the development of complications of overweight and obesity such as metabolic syndrome, type 2 diabetes mellitus, cardiovascular disease and osteopenia/osteoporosis ( 47 ). The associations between vitamin D status and insulin sensitivity parameters in obese pediatric population have been previously reported ( 12 , 48 53 ). The effects of vitamin D on glucose homeostasis, exerted mainly by its active form 1,25-dihydroxycholecalciferol, include the increase of peripheral and hepatic glucose uptake, the improvement in synthesis and secretion of insulin, the protection of β-cells from cytokine induced apoptosis and attenuation of inflammation ( 47 , 54 56 ).…”
Section: Discussionmentioning
confidence: 77%
“…( 62 ), among a group of more than one hundred obese children with 25(OH)D levels above or below 20 ng/ml, found higher total cholesterol and LDL-C levels in the group with vitamin D deficit. It should be noted that the stage of puberty also affects the relationship between vitamin D and the components of metabolic syndrome in obese children ( 53 , 70 , 71 ). Pires et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An adequate 1,25-dihydroxyvitamin D3 level is essential for normal insulin secretion[ 44 , 45 ]. Pires et al [ 46 ] showed that vitamin D deficiency in children with overweight or obesity increases the risk of IR during puberty.…”
Section: Risk Factors For Irmentioning
confidence: 99%